Certified OpenStack Administrator study guide : get everything you need for the COA exam - Markelov, Andrey (Certification study companion series., 2022)
Gain a better understanding of how to work with the modern OpenStack IaaS Cloud platform. This updated book is designed to help you pass the latest “Yoga” version of the Certified OpenStack Administrator (COA) exam from the Open Infrastructure Foundation. OpenStack is a cloud operating system that controls large pools of computer storage and networking resources throughout a datacenter. All exercises have been updated and re-written for the current version of the exam using the modern CLI tool. This book covers 100% of the exam requirements and each topic is taught using practical exercises and instructions for the command line and for the Horizon dashboard. All chapters are followed by review questions and answers. Even after you have taken and passed the COA exam, this book will remain a useful reference to come back to time after time.